NOWATORSKIE ROZWIĄZANIA W OLIMPIADZIE JĘZYKOWEJ. PERSPEKTYWA UCZNIA - Spychała-Wawrzyniak, Małgorzata (Neofilolog, 2018)
The aim of this article is to present a selection of novel tools used in organizing a foreign language competition. Particular attention will be focused on finalists’ and laureates’ opinions, expressed by means of a questionnaire administered for the needs of evaluation of innovative instruments used in the Spanish Language Competition. These include the Moodle platform, electronic tests, and a comprehensive website. Finally, we will present some recommendations for current and future organizers of foreign language competitions concerning the use of new technologies in their activities.